The impact of large volume atmospheric pressure air glow discharge plasma on enhancing denim fabric (textile) sewing process - Abdel-Aleam H. Mohamed; Ihab M. El-Sayed (Journal of Taibah University for Science, 2024)
A direct-current large-volume atmospheric pressure air glow discharge plasma (APAGDP) was developed to enhance the sewing process of denim fabric. The generated plasma was characterized optically, electrically, and spectroscopically. The generated plasma presents a positive electric resistance behaviour. The plasma emission spectra are dominated by the nitrogen second positive system. Its intensity increases with the applied voltage. The generated plasma was used as a pre-treatment to enhance the sewing of the denim fabric at different exposure times, from 5 to 600 s. The scanning electron microscopy images showed no damage to the surface morphology of the denim fabric after plasma treatment. The sound pressure level (SPL) was used to verify the plasma effect on the denim fabric as compared to the untreated fabric. The SPL decreases with plasma exposure time. This result indicates that the plasma improves the sewing performance of the denim fabric.